Cardiac Assist Devices: Early Concepts, Current Technologies, and Future Innovations - Jooli Han; Dennis R. Trumble (Bioengineering, 2019)
Congestive heart failure (CHF) is a debilitating condition that afflicts tens of millions of people worldwide and is responsible for more deaths each year than all cancers combined. Because donor hearts for transplantation are in short supply, a safe and durable means of mechanical circulatory support could extend the lives and reduce the suffering of millions. But while the profusion of blood pumps available to clinicians in 2019 tend to work extremely well in the short term (hours to weeks/months), every long-term cardiac assist device on the market today is limited by the same two problems: infections caused by percutaneous drivelines and thrombotic events associated with the use of blood-contacting surfaces. A fundamental change in device design is needed to address both these problems and ultimately make a device that can support the heart indefinitely. Toward that end, several groups are currently developing devices without blood-contacting surfaces and/or extracorporeal power sources with the aim of providing a safe, tether-free means to support the failing heart over extended periods of time.